Cloud storage security scheme for image encryption using modified morse and zigzag pattern - Thilagavathy, R.; Murugan, A. (International Journal of Engineering and Technology, 2019)
In the research of cloud storage security, the image encryption is given much attention and a lot of encryption algorithms have been proposed. The image encryption is different from the text encryption methods owing to some of features of images such as capacity and data redundancy. So, the image encryption is comparatively difficult to handle with traditional methods. In the proposed work, the image encryption and decryption are based on modified Morse code and diagonal zigzag pattern. To begin with, the pixels of image are extracted and then converted into binary form. The binary data is replaced by DNA sequence with modified Morse code and diagonal zigzag pattern. The proposed algorithm successfully encrypts/decrypts the image with DNA and modified Morse code with diagonal zigzag pattern. The encrypted image using the proposed algorithm is absolutely different when compared to original image file. So the encrypted image is suitable for the secured transmission over the cloud data storage. Thus, this proposed model provides an additional measure to tighten the image security efficiently.Â Â